Supply chain management strategy : using SCM to create greater corporate efficiency and profits - Oliveira, Alexandre (Pearson Education, 2014)
Drive more value from your supply chain by choosing and implementing the right models and strategies. Supply Chain Management Strategy offers expert guidance for comparing and choosing models, implementing governance, and strategizing to enable sales growth, margin growth, and superior customer experience. Lead authored by pioneering supply chain management expert Alexandre Oliveira, this guide focuses on driving maximum business value from modern supply chain strategies and models. Oliveira and senior supply chain executive Anne Gimeno thoroughly introduce the topic, offer detailed descriptions of each relevant model, and present modern applications and best practices drawn from the experiences of leading companies. Coverage includes: Adaptive, Triple-A, customer-driven, demand-driven, and resilient supply chains Assessing the strengths and weaknesses of each model in your unique context Implementing effective governance, including Sales and Operations Planning (SandOP), Integrated Business Planning (IBP), and Business Forecasting Capability (BFC) Performing effective supply chain continuity planning (BCP) Enabling growth in sales, revenue, and market share Accelerating revenue cycles and reducing lost sales Supporting marketing and sales initiatives Growing margins by reducing the cost of sales Balancing asset management, service level, cost structure, and other tradeoffs Delighting customers with the right service level at the right cost This guide's content will be exceptionally helpful for both practitioners and students, including participants in APICS and other leading certification programs.